Islamophobia and A proper understanding of Islam, A study of Bangladesh - Azmery Sultana (International Journal of Emerging Issues in Islamic Studies, 2022)
The emergence of Islamic organizations during the colonial era caused disunity among the Muslim Ummah in Nigeria. The quest to coordinate the affairs of these organizations and to unite the Muslim Ummah nationally under one umbrella led to the establishment of the Nigerian Supreme Council for Islamic Affairs (NSCIA) in 1973. This study, therefore, examines the role of NSCIA in addressing the challenges of disunity confronting the Muslim Ummah in Nigeria. Data were collected from oral interviews, questionnaires, and secondary sources. A multidisciplinary approach was adopted using a combination of historical, phenomenological, and sociological methods of data analysis. The theoretical framework is built on the theory of Asabiyyah by Ibn Khaldun and the theory of structural functionalism. The study discovered that the need to protect the Islamic faith from colonial influence gave rise to the emergence of Islamic organizations in Nigeria. It is also discovered that Nigerian Muslims are divided along ethnic, regional, and organizational lines. The study shows that despite the establishment of NSCIA in 1973 to foster unity, there are still issues bothering disunity among the Muslim Ummah in Nigeria. Perpetuation and nothernization of the council's leadership are discovered to be a factor responsible for the inefficiency of the Council in uniting the Ummah. This work recommends a review of the constitution of NSCIA for effectiveness. It also suggests rotation of its headship and that serious effort should be made by the Council to cultivate the spirit of unity among Muslims Ummah.